PEDAGOGICAL BASIS OF USING DIGITAL TECHNOLOGIES IN DEVELOPING COMMUNICATION SKILLS IN PRIMARY STUDENTS (Universal International Scientific Journal, 2026)
This article analyzes the role of digital pedagogical tools in the formation of communicative competencies of primary school students in the modern information society. The research highlights the communicative characteristics of children of primary school age and the methodological aspects of their activation through interactive educational platforms. The effectiveness of gamification and multimedia tools in the teaching process is also scientifically substantiated.
Keywords: : Digital pedagogy, communicative skills, Alpha generation, interactive methods, ICT, tablet education, multimedia presentations, communication culture.